Analysis and comparative evaluation of front-end technologies for web application development - Ilievska, Frosina; Gramatikov, Sasho (My University, 2022)
In this dynamic, ever-evolving world of web technology, many development tools are created. Everyone can agree that the programming language JavaScript is already in use and will continue to be popular in the future. Despite the many great JavaScript technologies over the past decade, Angular, React.js, and Vue.js remain the most popular. The construction of a modern single-page application is covered in this study, with an emphasis on the front-end in each of the technologies and the analysis of tests relating to the three key areas of performance, modularity, and usability where data may be evaluated and compared. By analyzing the test findings of the three aspects using the analytical hierarchy process approach, a comparison was produced. This paper provides a response to the question: Which JavaScript framework is best for developing single-page applications in terms of performance, modularity, and usability? In conclusion, React is the most suitable option for a simple single-page frontend application in our case.
Keywords: front-end comparison, JavaScript technologies, single-page application development, complexity analysis, analytical hierarchy process